O que Descartes tem a dizer sobre Foucault? As figuras do cartesianismo em História da loucura e em A hermenêutica do sujeito. - Yazbek, André Constantino (Dorsal. Revista de Estudios Foucaultianos)
This article aims to explore the proximities and distances between History of Madness (1961) and The Hermeneutics of the Subject (1982), works that span more than twenty years of Foucault’s research, focusing on how Foucault engages with the figures of «Descartes» and «Cartesianism» at these two crucial moments of his intellectual trajectory. In this regard, we seek to develop the hypothesis that «Cartesianism» serves, in Foucault’s work, as a discursive object whose treatment allows for the delineation of turning points in what might be called a history of the subject’s relationship with truth.